Outcome measures in periodontal management at primary care dental clinic / Nuryastri Md. Mustafa - Nuryastri , Md. Mustafa (2018)
Periodontal disease is a highly prevalent and the most common oral disease affecting adults. An overwhelming body of evidence shows that personal and professional plaque control are essential for the prevention and treatment of the disease. Despite the evidence, there is an absence of a simplified task-oriented approach or a care pathway for managing patients with periodontal disease at primary care dental clinics in Malaysia. Thus, the objectives of this study were, 1) To develop a periodontal care pathway for managing patients with periodontal disease at primary care dental clinics in Malaysia, 2) To assess and compare between patients treated according to the periodontal care pathway and current practice in terms of improvement in oral hygiene practice, bleeding on probing, plaque scores, probing pocket depth (PPD), and oral health-related quality of life (OHRQoL) after 10 weeks, and 3) To determine the distribution of cost for managing patients with periodontal disease between the two methods. The steps for evidence-based practice was used in the development of the clinical pathway. The effectiveness of the periodontal care pathway in treating periodontal disease in adults was evaluated using a randomised controlled trial (RCT) with 124 participants randomly allocated to the clinical pathway (intervention) and current practice (control) groups. The effect of the care pathway on oral hygiene practice, clinical, and OHRQoL outcomes (using OHIP-14) were compared with the current practice at baseline and after 10 weeks. Intention To Treat (ITT) analysis was used in data analysis. A cost analysis was carried out using the top down and bottom up methods for both groups. Finally, the proposed consensus-based periodontal care pathway was developed and used in this clinical trial. Sixty two participants were analysed in each group. Both groups were not statistically significance at baseline. There was a significant difference in the number of participants who reported interdental cleaning (p<0.001) and confidence in performing effective tooth brushing (p<0.05) after 10 weeks compared to baseline in the intervention group. Both groups had significant reductions in bleeding scores and plaque scores (p<0.001) after 10 weeks with greater reductions in the intervention group. The between-group difference in mean decrement for bleeding score was 8.7% (95%CI:14.54-2.92; p=0.004), for plaque score it was 5.2% (95%CI:10.60-0.18; p=0.058). The reduction of sites with PPD 4-5mm was not significant in both groups after 10 weeks. A significant improvement in quality of life was observed in the intervention group after 10 weeks associated with the self-conscious domain (p=0.039). The total provider cost for the clinical pathway was RM86.30 while in the current practice it was RM30.00. The findings provide some evidence that the use of the proposed periodontal care pathway for treating periodontal patients in primary care dental clinics had significantly improved the interdental cleaning practice and confidence of participants in performing effective tooth brushing. It also resulted in a significantly higher reduction in bleeding scores and plaque scores compared to the current practice, respectively. The higher provider cost in the periodontal care pathway was attributed to the longer time for delivering oral hygiene instructions.